A Matter of Taste: The Negative Welfare Effect of Expert Judgments - Nicolas Lagios; Pierre-Guillaume Méon (CESifo GmbH, 2024)
We study how experts influence consumer behavior and welfare by focusing on the Booker Prize. Leveraging the discontinuity created by the attribution of the prize, we show that readers receive the signal sent by the jury of the Booker and are persuaded to buy the awarded book but experience lower satisfaction due to a misalignment between their tastes and those of the jury. Calibrating a structural model of demand, we find that the prize reduces consumer surplus by 70,039 annually, meaning that a consumer buying an awarded book experiences a loss in surplus of 8% of the book's average price.
Keywords: D12; D83; L15; L82; Z11; 330; awards; prizes; welfare; sales; experts; books; consumer surplus